EU administrative law - Craig, P. P. (Paul P.) (Oxford : Oxford University Press, 2012)
This is a legal evaluation of the ways in which the EU delivers policy. It assesses the role of law therein from a contextual and inter-disciplinary perspective and considers in-depth the principles of EU judicial review applicable to EU administration and that of the Member States.
Previous ed.: 2006.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Administrative law -- European Union countries